A newfangled study using risk silhouette and uncertainty approximation for quantification of acyclovir in diverse formulation - Karan Mittal; Riddhish Patadia; Chintan Vora; Rajashree C. Mashru (Elsevier, 2015)
Risk assessment and uncertainty approximation are two major and important parameters that need to be adopted for the development of pharmaceutical process to ensure reliable results. Additionally, there is a need to switch from the traditional method validation checklist to provide a high level of assurance of method reliability to measure quality attribute of a drug product. In the present work, evaluation of risk profile, combined standard uncertainty and expanded uncertainty in the analysis of acyclovir were studied. Uncertainty was calculated using cause-effect approach, and to make it more accurately applicable a method was validated in our laboratory as per the ICH guidelines. While assessing the results of validation, the calibration model was justified by the lack of fit and Levene×³s test. Risk profile represents the future applications of this method. In uncertainty the major contribution is due to sample concentration and mass. This work demonstrates the application of theoretical concepts of calibration model tests, relative bias, risk profile and uncertainty in routine methods used for analysis in pharmaceutical field. Keywords: Acyclovir, Risk profile, Relative bias, Combined standard uncertainty, Expanded uncertainty